Anoctamin 1-A member of a novel family of ion channels with extended functions and significance in disease - Lérias, Joana Ramos Rapaz, 1988- (2018)
Tese de doutoramento, Biologia (Biologia de Sistemas), Universidade de Lisboa, Faculdade de Ciências, 2018